2018
DOI: 10.1056/nejmoa1803238
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a Cluster of Sphingomonas koreensis Infections

Abstract: BACKGROUND Plumbing systems are an infrequent but known reservoir for opportunistic microbial pathogens that can infect hospitalized patients. In 2016, a cluster of clinical sphingomonas infections prompted an investigation. METHODS We performed whole-genome DNA sequencing on clinical isolates of multidrug-resistant Sphingomonas koreensis identified from 2006 through 2016 at the National Institutes of Health (NIH) Clinical Center. We cultured S. koreensis from the sinks in patient rooms and performed both wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
52
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 41 publications
1
52
0
2
Order By: Relevance
“…17 Four of the S. koreensis patient isolates had high genomic similarity to each other (>99.9% average nucleotide identity (ANI)) and to environmental S. koreensis isolates from water and faucet samples collected from inside patient rooms (>99.7% ANI). 17 This genomic similarity suggested that there was a common environmental reservoir for this pathogen that had persisted in the hospital infrastructure over time. 17 Further, banked S. koreensis isolates from 2006 also showed high similarity to isolates from the 2016 outbreak (>99.8% ANI), suggesting this reservoir had persisted for a decade.…”
Section: Using Genomics To Better Track Outbreaks and Monitor Reservomentioning
confidence: 98%
See 4 more Smart Citations
“…17 Four of the S. koreensis patient isolates had high genomic similarity to each other (>99.9% average nucleotide identity (ANI)) and to environmental S. koreensis isolates from water and faucet samples collected from inside patient rooms (>99.7% ANI). 17 This genomic similarity suggested that there was a common environmental reservoir for this pathogen that had persisted in the hospital infrastructure over time. 17 Further, banked S. koreensis isolates from 2006 also showed high similarity to isolates from the 2016 outbreak (>99.8% ANI), suggesting this reservoir had persisted for a decade.…”
Section: Using Genomics To Better Track Outbreaks and Monitor Reservomentioning
confidence: 98%
“…17 This genomic similarity suggested that there was a common environmental reservoir for this pathogen that had persisted in the hospital infrastructure over time. 17 Further, banked S. koreensis isolates from 2006 also showed high similarity to isolates from the 2016 outbreak (>99.8% ANI), suggesting this reservoir had persisted for a decade. 17 These studies demonstrate the capabilities of WGS in tracking individual strains in outbreaks.…”
Section: Using Genomics To Better Track Outbreaks and Monitor Reservomentioning
confidence: 99%
See 3 more Smart Citations